Badania mineralogiczno–chemiczne mineralizacji chrząstki stawowej na przykładzie chrząstki stawu biodrowego człowieka - Olejarz, Aneta (My University, 2011)
The master’s thesis was devoted to research of articular cartilage that was removed from heads of femur with mineralogical – chemical methods. Material to research came from 9 patients who underwent arthroplasty surgery. The articular cartilage was observed the form of phosphates and oxalates mineralization. There were also made attempts cube of collagen with laboratory test.

Pracę poświęcono badaniom mineralogiczno – chemicznym chrząstek stawowych, usuniętych z głów kości udowych. Materiał badawczy pochodził od 9 pacjentów, którzy zostali poddani zabiegowi endoprotezoplastyki stawu biodrowego. W chrząstkach stawowych zaobserwowano mineralizację w postaci fosforanów wapnia i szczawianów. Podjęto także próby badania kostek kolagenowych metodami laboratoryjnymi.
Mineralogical–chemical research mineralization of articular cartilage on the example of cartilage in human hip-joint
Keywords: chrząstka stawowa; mineralizacja; fosforany wapnia; szczawiany; kolagen; articular cartilage; mineralization; pfosphates; oxalates; collagen